PEMBELAJARAN TEMATIK TERPADU DENGAN MODEL COOPERATIVE LEARNING TIPE TALKING STICK DI SEKOLAH DASAR - Vivi Novita Mayesi Putri. K; Arwin Arwin (Universitas Negeri Padang, 2022)
The research is motivated by student learning outcomes in integrated thematic learning in class IV SDN 01 Benteng Pasar Atas Kota Bukittinggi is still low. The aim of the study was to improve student learning outcomes in integrated thematic learning with the Cooperative Learning Model Talking Stick in Class IV SDN 01 Benteng Pasar Atas Kota Bukittinggi. The results of the study show that planning, implementation and learning outcomes have increased. The RPP assessment of the first cycle was 74,97% and in the second cycle it increased to 97,22%. The evaluation of the implementation of teacher activities in the first cycle was 78% and increased in the cycle of 97%. For the activities of students in the first cycle 75% increased in the cycle of 95%. %. Assessment of student learning outcomes in the first cycle was 75 and increased in the second cycle 87. In conclusion, Cooperative Learning Type Talking Stick can improve student learning outcomes in integrated thematic learning learning in class IV SDN 01 Benteng Pasar Atas Kota Bukittinggi.